C1s protects cutaneous squamous carcinoma cells from TRAIL-induced apoptosis - Salmela, Maria; Nissinen, Liisa; Rappu, Pekka; Viiklepp, Kristina; Ojalill, Marjaana; Heino, Jyrki; Riihilä, Pilvi; Kähäri, Veli-Matti (Springer Science and Business Media LLC, 2026)
Cutaneous squamous cell carcinoma (cSCC) is the most common metastatic skin cancer. The prognosis of the metastatic cSCC is poor, and there are no established biomarkers to predict metastasis risk, nor specific targeted therapies for advanced or metastatic cSCC. Previous studies have demonstrated that the complement serine proteinase C1s promotes cSCC growth both in culture and in vivo by modulating apoptotic signaling. Here, we investigated the mechanistic role of C1s in regulating apoptosis by examining its impact on cell surface proteome of cSCC cells. Mass spectrometric analysis of cell surface proteins following silencing of C1s identified TRAIL receptor 1 (DR4) as a candidate target, showing increased accumulation at the cell surface. This finding was validated using cell surface biotinylation and western blot analysis in both siRNA-mediated C1s knockdown and CRISPR/Cas9-generated C1s knockout cells. Functionally, high endogenous levels or forced overexpression of C1s conferred resistance to TRAIL-induced apoptosis in cSCC cells, whereas reduced C1s levels sensitized cells to apoptotic signaling. These findings suggest that upregulation of complement C1s in cSCC not only contributes to tumor progression but also serves as a protective mechanism against TRAIL-induced apoptosis, highlighting its potential as a therapeutic target and biomarker in aggressive cSCC.